How Family Forest Owners Consider Timber Harvesting, Land Sale, and Conservation Easement Decisions: Insights from Massachusetts, USA - Zhao Ma; David B. Kittredge (International Journal of Forestry Research)
Ten million family forest owners own 35 percent of US forestland. Although one owner's action may be insignificant, many owners' decisions across the landscape and over time can together affect the forest ecosystem. By analyzing survey data from Massachusetts, this paper examines the thought processes of family forest owners when considering timber harvesting, land sale, and conservation easement decisions, all having great potential to shape the future of individual properties and forest landscape. Some factors (e.g., attitudes towards forestland and desire for and experience of cooperation) were important for engaged and unengaged owners, some factors (e.g., attained education level, age, and absenteeism) were irrelevant, and some factors (e.g., acreage and information sources) had mixed effects depending on the decision and landowner engagement level. The results suggest the need to avoid any one-size-fits-all approach, differentiate landowners based on their engagement level, and tailor outreach efforts to address the interests and concerns of particular audiences.